Experimental assessment of the performance of ablative heat shield materials from plasma wind tunnel testing - Löhle, S; Hermann, T; Zander, F (Springer, 2017)
A method for assessing the performance of typical heat shield materials is presented in this paper. Three different material samples, the DLR material ZURAM, the Airbus material ASTERM and the carbon preform CALCARB were tested in the IRS plasma wind tunnel PWK1 at the same nominal condition. State of the art diagnostic tools, i.e., surface temperature with pyrometry and thermography and boundary layer optical emission spectroscopy were completed by photogrammetric surface recession measurements. These data allow the assessment of the net heat flux for each material. The analysis shows that the three materials each have a different effect on heat flux mitigation with ASTERM showing the largest reduction in surface heat flux. The effect of pyrolysis and blowing is clearly observed and the heat flux reduction can be determined from an energy balance.